¿Are we interpreting the language of the pots? - Dolorier Torres, Camilo (2024)
Some existing methodological approaches for the analysis of archaeological ceramics are evaluated, and the need to standardize criteria is reflected on. Ceramics are understood as a goods derived from a production process in which each product contains technological knowledge reflected in its quality. Furthermore, each object or artifact also reveals the formal and identity expression of a community from a particular era, externalizing a style. Likewise, as a consumer good it adopts intangible values intrinsic to social work such as, for example, satisfying a need in its functional, ideological, economic or social expression. These three dimensions of analysis: technological, cultural identity and social valuation define its essence. In the technological dimension, ceramic production involves a succession of technical steps. Therefore, ceramic study must analytically reproduce this succession of steps to understand the technical particularities of each production process.